Migration and Cultural Identity in Ulster and Southwest Scotland, 1690-1715 - Middleton, Katherine (Trinity College Dublin, 2007)
The 1690s probably saw the largest migration from Scotland to Ulster in any single decade. Fifty thousand is a conservative estimate that is frequently quoted. The movement of such a number of people reshaped both places - origin and destination. In Scotland, this would have meant something like one in twenty people leaving by the end of the decade, with a much higher regional impact in the southwest. In Ulster, the alteration in the demographic balance fuelled fears that the established church and English gentry would be forced to cede control to a horde of Scottish presbyterians. The 'people with no name' as the American historian Patrick Griffin calls the Scots in Ulster, have an added significance in that something like 100,000 of them moved on to North America later in the eighteenth century. Despite the massive social impact that movement on this scale implies, the period 1690 to 1715 remains surprisingly understudied. This study is not primarily a statistical analysis but an examination of the experience of migration in terms of identity, cultural adaptation, and relationships with existing communities.
Exhibited at the second Glucksman Memorial Symposium on June 13th 2007
Keywords: Ulster -- seveteenth and eighteenth centuries; Southwest Scotland -- seveteenth and eighteenth centuries; Migration